THE IMPACT OF VOCABULARY SELF- COLLECTION STRATEGY ON STUDENTS’ READING SKILL AT JUNIOR HIGH SCHOOL - HOTRINA P SILALAHI (Journal of Education, Linguistics, Literature and Language Teaching, 2025)
The purpose of this study was to investigate the effectiveness of the Vocabulary Self-Collection Strategy (VSS) in enhancing students' reading skills at SMPN 5 Langsa. This study used a quantitative experimental research method with a pre-test and post-test design on a single group. The population in this study includes all ninth-grade students at SMPN 5 Langsa, which consists of four classes. The sample of this study consisted of class IX-4, which amounted to 24 students and was selected using a purposive sampling technique. In collecting data, researchers used reading tests in the form of multiple choices using descriptive text material. The results showed an increase in students' reading skills. The increase in students' vocabulary can affect the improvement of students' reading comprehension. This is evidenced by the significant increase in students' pre-test and post-test scores. The student’s average score increased from 37.78 (pre-test) to 75.00 (post-test). Furthermore, the results of the paired sample t-test analysis indicate that the Sig. value (two-tailed) is 0.000, which is less than 0.05. This means that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Thus, this study shows that the implementation of the Vocabulary Self-Collection Strategy has a positive impact on improving students' reading skill.